Handling of computational in vitro/in vivo correlation problems by Microsoft Excel: I. principles and some general algorithms - Langenbucher, Frieder (European journal of pharmaceutics and biopharmaceutics, 2002)
Most computations in the field of in vitro/in vivo correlations can be handled directly by Excel worksheets, without the need for specialized software. Following a summary of Excel features, applications are illustrated for numerical computation of AUC and Mean, Wagner–Nelson and Loo–Riegelman absorption plots, and polyexponential curve fitting.